2019
DOI: 10.3390/ijms20030659
|View full text |Cite
|
Sign up to set email alerts
|

CD200 Modulates S. aureus-Induced Innate Immune Responses Through Suppressing p38 Signaling

Abstract: Rapid activation of macrophages plays a central role in eliminating invading bacteria as well as in triggering the inflammatory responses, but how the anti-bacterial and the inflammatory responses are coordinated, in terms of macrophages, is not completely understood. In this study, we demonstrated that Staphylococcus aureus (S. aureus) induced the expression of CD200 in murine macrophages in a dose-dependent manner. We found that CD200 significantly suppressed the S. aureus-induced production of nitric oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…Activating CD200/ CD200R signaling may be insufficient to contain the NF-κB pathway after stroke in vivo. Recent studies reported that the CD200/CD200R pathway modulated the inflammatory response by controlling MAPK activation in vitro and in vivo [49][50][51]. The current results showed that CD200Fc inhibited MAPK activation by suppressing the phosphorylation of p-JNK and p-p38 after stroke.…”
Section: Discussionsupporting
confidence: 56%
“…Activating CD200/ CD200R signaling may be insufficient to contain the NF-κB pathway after stroke in vivo. Recent studies reported that the CD200/CD200R pathway modulated the inflammatory response by controlling MAPK activation in vitro and in vivo [49][50][51]. The current results showed that CD200Fc inhibited MAPK activation by suppressing the phosphorylation of p-JNK and p-p38 after stroke.…”
Section: Discussionsupporting
confidence: 56%
“…In steady-state lung, AMs are in an immunosuppressed state and their phenotype is tightly control by the lung microenvironment. They express high level of CD200 receptor (CD200R) which is associated with M2 phenotype ( 42 , 43 ) and are involved in the downregulation of immune inflammation ( 44 , 45 ). This may be important for tolerating innocuous inhaled agent.…”
Section: Amsmentioning
confidence: 99%
“…Cd200r1 encodes a cell surface glycoprotein that downregulates pro-inflammatory signaling ( 29 , 46 ). Additionally, Chen et al showed that CD200, the ligand of CD200R1, triggers phagocytosis ( 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…We explain these discrepancies with the higher cellular complexity of PCLS in which individual and cell-type specific dependencies may be masked. The involvement of CD200R1 in the uptake of live P. aeruginosa was surprising knowing its well-established function as inhibitor of pro-inflammatory signaling ( 29 , 46 , 68 ). Our first assumption that heat-killed P. aeruginosa is not able to overcome the limiting actions of CD200R1 reflecting in a diminished pro-inflammatory cytokine profile did not prove as being true.…”
Section: Discussionmentioning
confidence: 99%